2015
DOI: 10.1136/annrheumdis-2015-eular.4742
|View full text |Cite
|
Sign up to set email alerts
|

FRI0439 The Role of the Myeloid Inflammatory Bone Marrow Compartment in Onset and Progression of Myocardial Fibrosis in Systemic Sclerosis

Abstract: BackgroundOne of the major causes of death in systemic sclerosis (SSc) patients is heart involvement which phenotypically resembles inflammatory dilated cardiomyopathy (iDCM) [1]. Recent investigations in animal models of iDCM have demonstrated that the main source of pathological myofibroblasts originates from the bone marrow [2].ObjectivesWe hypothesized that the monocyte/macrophage compartment is responsible for the onset and progression of myocardial fibrosis in SSc. Therefore, we studied the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…35) Studies have also shown that TGF-β1 can stimulate CFs to transform into myofibroblasts, induce CFs to synthesize matrix metalloproteinases, and cause ventricular remodeling. 36) To reduce MF after MI, extensive studies have investigated the mechanisms of MF MI. 37) LncRNAs can regulate gene expression, sponge miRNAs, and regulate cell transcription and translation.…”
Section: Discussionmentioning
confidence: 99%
“…35) Studies have also shown that TGF-β1 can stimulate CFs to transform into myofibroblasts, induce CFs to synthesize matrix metalloproteinases, and cause ventricular remodeling. 36) To reduce MF after MI, extensive studies have investigated the mechanisms of MF MI. 37) LncRNAs can regulate gene expression, sponge miRNAs, and regulate cell transcription and translation.…”
Section: Discussionmentioning
confidence: 99%